Economic adversity and crime: old theories and new evidence. Issue 1 (April 2015) - Weatherburn, Don; Schnepel, Kevin T.
Abstract : In this article we make a case for the continuing relevance of economic adversity and social policy in the understanding and prevention of crime. We begin by discussing early theories positing a causal relationship between economic adversity and crime and examine the factors that have led to a loss of confidence in these theories. We then summarise two prominent strands of research investigating important indirect criminogenic effects of economic adversity. The first deals with the long‐term impact of economic adversity on parenting. The second analyses the impact of economic adversity on crime through its effect on informal social controls within a community. Finally, we review recent empirical studies that use modern econometric techniques to explore the direct effects of economic adversity on crime, highlighting research focused on factors such as wages, employment, housing, and income support programs. The paper concludes by suggesting a number of areas for future research.